PELAKSANAAN PEMBELAJARAN DI SDIT BINTANG CENDEKIA PEKANBARU (Studi Deskriptif Bagi Siswa Autis) - Puspita, Melisa Indah Puspita Indah; Kurniaman, Otang Kurniaman Otang; Marhadi, Hendri Marhadi Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the realization that the importance placement of students with autism and implementation of learning for students with autism inclusive schools are still not as it should be. This resulted students with autism do not get the education that is optimal, it may indicate by various factors. Therefore, it is necessary to study the form of learning by case study on the implementation in inclusive school. The study was conducted in the form of descriptive in order to determine the implementation of learning for students with autism in SDIT Bintang Cendekia Pekanbaru. The study was conducted in two classes for two days in each class. The data was obtained from the teachers observation in implementing the learning activities in the classroom and from interviews with relevant sources. Research done by set a specific number of variables and describe all learning activities in schools without exception. Learning is done by placing autistic students in the regular classroom and providing assisting teacher. Learning as generally happens in the case of teacher evaluations only provide adjustment time to students with autism. Results from this study is that the arrangement of space in a class on the implementation of learning meets the criteria class that friendly for students with autism, while learning implementation is still not optimal since the school have not implemented the PPI (Individual Education Program) for students with autism, and evaluation are still not implemented. Based on these results it can be concluded that the implementation of thelearning for students with autism in SDIT Bintang cendekia has not done well.Key Word : Learning for Autism Student